The Effect of Light Spectrum on the Morphology and Cannabinoid Content of Cannabis sativa L. - Gianmaria Magagnini; Gianpaolo Grassi; Stiina Kotiranta (Medical Cannabis and Cannabinoids)
Cannabis sativa L. flowers are the main source of Δ-9-tetrahydrocannabinol (THC) used in medicine. One of the most important growth factors in cannabis cultivation is light; light quality, light intensity, and photoperiod play a big role in a successful growth protocol. The aim of the present study was to examine the effect of 3 different light sources on morphology and cannabinoid production. Cannabis clones were grown under 3 different light spectra, namely high-pressure sodium (HPS), AP673L (LED), and NS1 (LED). Light intensity was set to ∼450 µmol/m2/s measured from the canopy top. The photoperiod was 18L: 6D/21 days during the vegetative phase and 12L: 12D/46 days during the generative phase, respectively. At the end of the experiment, plant dry weight partition, plant height, and cannabinoid content (THC, cannabidiol [CBD], tetrahydrocannabivarin [THCV], cannabigerol [CBG]) were measured under different light treatments. The experiment was repeated twice. The 3 light treatments (HPS, NS1, AP673L) resulted in differences in cannabis plant morphology and in cannabinoid content, but not in total yield of cannabinoids. Plants under HPS treatment were taller and had more flower dry weight than those under treatments AP673L and NS1. Treatment NS1 had the highest CBG content. Treatments NS1 and AP673L had higher CBD and THC concentrations than the HPS treatment. Results were similar between experiments 1 and 2. Our results show that the plant morphology can be manipulated with the light spectrum. Furthermore, it is possible to affect the accumulation of different cannabinoids to increase the potential of medicinal grade cannabis. In conclusion, an optimized light spectrum improves the value and quality of cannabis. Current LED technology showed significant differences in growth habit and cannabinoid profile compared to the traditional HPS light source. Finally, no difference of flowering time was observed under different R:FR (i.e., the ratio between red and far-red light).